A multi-scale energy systems engineering approach towards integrated multi-product network optimization. (1st January 2021) - Demirhan, C. Doga; Tso, William W.; Powell, Joseph B.; Pistikopoulos, Efstratios N.
Abstract: 21 st century energy production, conversion, and delivery systems need to go through a transition to be less carbon-intensive while meeting an increasing energy demand. In a more and more interconnected world, energy systems of various sectors (e.g. power, fuels, chemicals, etc.) go through this transition via shifting the primary energy sources from carbon-intensive fossil-fuels to renewable and sustainable resources. With this study, we present a multi-scale strategy for optimal design and operation of multi-product process systems that can produce power, synthetic fuels, chemicals, and energy carriers from renewable and fossil resources. This multi-scale approach combines process synthesis, scheduling, and supply chain concepts in a mixed-integer linear programming model to address the trade-offs between integrating various fossil and renewable technologies. Our strategy is applied to integration of low-emission (i) synthetic liquid transportation fuels, (ii) hydrogen, (iii) ammonia, (iv) methanol, and (v) renewable power production from natural gas, solar, and wind energy at a location in Amarillo, Texas. Case study results show that with our approach various energy systems can be modeled either separately and integrated with the same common representation. Sectors integration to produce low-emission products in the same facility can result in 17% reduction in total production costs. While solar and wind energy are favorable to produce renewable power, current state-of-the-art methane conversion technologies are more favorable to produce hydrogen and hydrogen-based products. Graphical abstract: Highlights: MILP model for multi-scale simultaneous design and operation optimization. Integration of solar, wind, and natural gas conversion pathways. Case studies for Texas on power, synthetic fuels, and chemicals production. Systems integration results in cost savings in hydrogen and power subsystems.